Dynamic behaviors of a modified computer virus model: Insights into parameters and network attributes - Ahmad I.; Bakar A.A.; Jan R.; Yussof S. (Elsevier B.V., 2025)
Securing computers is crucial to prevent data breaches, identity theft, and financial losses. Virus incursions disrupt operations, causing downtime and costly repairs. Protective measures, including anti-virus software and cybersecurity practices, maintain network integrity and reduce the spread of malware. Combining robust cybersecurity with green computing strategies ensures efficient energy usage and sustainable network environments, safeguarding against viruses while contributing to both security and environmental goals In this study, we explore the dynamic behaviors of a modified version of the computer virus model and elucidate the connection between its parameters and network attributes. We employ Banach's and Schaefer's fixed-point theorems to assess the existence and uniqueness of solutions of the suggested model. Furthermore, we establish sufficient conditions for Ulam?Hyers stability within the envisioned computer virus model. To analyze solution trajectories and the impact of various input factors on computer virus dynamics, we utilize an efficient numerical technique, providing insight into the relationships between model parameters and enabling the design of networks that minimize the risk of virus outbreaks under various bifurcation conditions. ? 2024 Faculty of Engineering, Alexandria University